Home of Alexander Henderson Galloway at 137 North Cherry Street. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo taken in the 1910s.
Home of Alexander Henderson Galloway at 137 North Cherry Street. Galloway married Mary Elizabeth (Mamie) Gray.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth